SOSIALISASI PENCEGAHAN BULLYING MELALUI METODE EDUKASI PARTISIPATIF DAN DRAMA INTERAKTIF BAGI SISWA SD NEGERI 1 KABEKELAN PREMBUN - Abror Muchlas; Bagas Candra Ardianto; Angga Prahara; Hendra Deni Pamungkas; Lulu Ma’rufah; Meylisa Nur Layli; Rizki Nur Yadi; Siti Mir’atul Ma’rifah; Sri Nur Fitriani; Sugeng Lestari; Wahib Mawahiburrohman (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Bullying in the elementary school environment is a serious problem that has a negative impact on children's psychological, cognitive, and social development. State Elementary School 1 Kabekelan Prembun was identified as having the potential for bullying cases that have not been optimally managed due to a lack of systematic understanding of prevention and handling. These information and assumptions were obtained from the results of observations made by the UMNU Kebumen Community Service Team before determining the target objects of socialization activities. This community service program aims to increase students' understanding and awareness of the dangers of bullying through participatory and interactive socialization methods, namely participatory education and interactive drama. The implementation method includes three stages: preparation, implementation, and evaluation. The results of the evaluation through the Bullying behavior data card that have been experienced by students show that students' understanding of bullying behaviors that have been experienced before the socialization activity was held, students did not understand the definition, form, impact, and strategies for preventing and handling Bullying. This program is expected to be an initial model for developing sustainable anti-bullying policies in schools.